Dynamics of irradiation: From molecules to nano-objects and from material science to biology - Wopperer, P.; Dinh, P. M.; Reinhard, Paul-Gerhard; Suraud, E. (Journal of Physics: Conference Series, 2013)
We give a brief review of theoretical and computational tools developed for the description and analysis of irradiation dynamics of cluster and molecules. We illustrate the capabilities of the method on the demanding example of C 60 irradiated by various laser fields. © Published under licence by IOP Publishing Ltd.
CRIS-Team Scopus Importer:2023-07-24